The Theme of “A New Lost Generation” in the Production of Prešov National Theatre - Knopová Elena (Slovenské divadlo)
The authoress elucidates the concepts of generations and generational affiliation, while focusing on various names and characteristics referring to a group of young people born during the 1980s and early 1990s. She introduces Generation Y, also called Millennials, and gives a short characteristic of a generation referred to as the Lost Generation, the Set-aside Generation, the Scarred Generation. She captures the external manifestations of the generation together with inner mechanisms and motives resulting in these manifestations. Using the example of Prešov National Theatre (PND) and its production, she introduces a new concept referred to as “A New Lost Generation”. The authoress endeavours to define it in Slovak context through the partial analyses of the plays included in Prešovská trilógia (Single radicals (2013), Kindervajco (2015), Good place to die (2015), [Prešov Trilogy (Single Radicals (2013), The Kinder Egg (2015), A Good Place to Die (2015)].